2009
DOI: 10.1353/csd.0.0053
|View full text |Cite
|
Sign up to set email alerts
|

Blue-Collar Scholars?: Mediators and Moderators of University Attrition in First-Generation College Students

Abstract: Many college entrants’ parents do not have college degrees. These entrants are at high risk for attrition, suggesting it is critical to understand mechanisms of attrition relative to parental education. Moderators and mediators of the effect of parental education on attrition were investigated in 3,290 students over 4 years. Low parental education was a risk for attrition; importantly, college GPAs both moderated and mediated this effect, and ACT scores, scholarships, loans, and full-time work mediated this ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
131
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(136 citation statements)
references
References 33 publications
2
131
0
Order By: Relevance
“…Some US literature indicates that first-generation students have lower achievement than their continuing-generation peers (Martinez et al, 2009;Pascarella et al, 2004). The present study indicates that the achievement outcomes of FIF and non-FIF are similar in the first year of study, but that achievement decreases for FIF in subsequent years of study.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Some US literature indicates that first-generation students have lower achievement than their continuing-generation peers (Martinez et al, 2009;Pascarella et al, 2004). The present study indicates that the achievement outcomes of FIF and non-FIF are similar in the first year of study, but that achievement decreases for FIF in subsequent years of study.…”
Section: Discussionsupporting
confidence: 54%
“…Some studies found no differences (Inman & Mayes, 1999;Strage, 1999) or that Grade Point Average (GPA) was influenced by prior academic preparation (Choy, 2001). Other studies indicated lower GPAs for first-generation students (Martinez, Sher, Krull, & Wood, 2009;Pascarella et al, 2004).…”
Section: United States Research On First-generation Studentsmentioning
confidence: 91%
“…For instance, Butler (2007) reports that the effects of paid work on college educational outcomes depend on job characteristics, with those jobs that are congruent in content with the major pursued and/or offering substantial control over work activities having a positive effect on academic outcomes, whereas other jobs with high burdens of work hours and demands exerting a negative influence on these outcomes. Converging with this pattern is the finding that among a large sample of college students, full-time work increases the risk of dropping out, whereas part-time work reduces this risk (Martinez et al 2009). …”
Section: Empirical Evidence Regarding the Consequences Of Working Durmentioning
confidence: 92%
“…They stated that institutional attachment, a core construct of Baker and Syrik's (1989) model of college adjustment, was the strongest available predictor of retention, accounting for 7.6% of the variance. Researchers have shown that academic adjustment, another component of Baker and Syrik's model, was associated with grade point average (Hezlett et al, 2001), which in turn was related to attrition (Martinez, Sher, Krull, & Wood, 2009). In addition, poor overall adjustment heightened the risk of alcohol-related negative consequences among college students (LaBrie, Ehret, Hummer, & Prenovost, 2012).…”
Section: Discussionmentioning
confidence: 99%